The quality of contemporary records made by handwriting. Comparative analysis over the period of nineteen years - Zieniewicz, Iwona (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Handwriting is a method to express and preserve thoughts by means of graphic signs. In the investigative and judicial practice, it is treated as an individual creation used for identification purposes in case of doubts over the authenticity of a written record. Nowadays, however, writing by hand is not the only way of conveying information, which results in moving away from this traditional method in favour of modern solutions. In the future, this tendency may limit the possibility to identify the author of a record on the basis of a handwritten record. Therefore, the purpose of this publication is to check whether contemporary handwritings show any signs of deterioration in the quality of handwritten records.
Keywords: pismo ręczne; cechy pisma ręcznego; analizy pisma ręcznego